Mecanismos alelopáticos como estratégia de manejo envolvendo espécies de cobertura vegetal - Mauli, Marcia Maria (2013)
This trial aimed at isolating and identifying secondary compounds of winter cover crops as black oats, turnip and hairy vetch in order to meet the growing need for healthy products that do not harm the environment. It also enlarges the management knowledge of such crops to demonstrate their advantages on weed control and stimulate the use of a correct no-tillage system, since there is some evidence of their allelopathic potential. Parameters that help on elucidating decomposition of plant residues and releasing allelochemicals to inhibit Bidens pilosa have been evaluated as inhibition percentage according to the amount of mass, which used the amounts of 10, 20, 30, 40 and 50 g, equivalent to 7.5, 15, 22.5, 30 and 37.5 t ha -1, and as well as the control treatment (no mass cover). It was also evaluated influence of field capacity on the wastes decomposition, with 50 and 70% of available water plus the control (100%). There was some releasing of allelochemicals by permanence of plant material on the soil in order to evaluate their respective periods of vegetable permanence: 0, 2, 4, 6 and 8 weeks and the application of soil solution where cover crops were cultivated, which were tested in a concentrated way and at the following dilutions 100, 200, 300 and 400 mL L- 1, as well as the control. In all tests, emergence (inhibition emergence percentage, emergence speed index - ESI and emergence speed - ES) during 10 days and initial development (fresh and dry weight of shoot and root) during 30 days were evaluated. Five seeds or seedlings have been used in pot and 20 of them in gerbox, with three replications. The secondary compounds were obtained by exhaustive extraction during seven days, isolated by column chromatography by wet (CCW) and identified by nuclear magnetic resonance (NMR). The main chemical groups in plants were also identified through techniques such as fingerprint and phytochemical screen. The experimental design was completely randomized. Quantitative data were submitted to variance analysis to check significance and were submitted to regression analysis. The qualitative data were submitted to average comparison by Tukey test at 5 % probability. Generally, the greater residue amount on soil, the greater is B. pilosa inhibition. The best regarding water content in soil is that the result must range between 70 and 50%, which is when the greatest inhibitions occurred. During the evaluation of decomposition periods, there was greater interference on sterilized soil and the residue management than the period itself. Thus, the most significant results were found in no sterilized soil and residue incorporation. The soil solution showed considerable changes in B. pilosa emergence only during the last sampling collections, especially in oilseed radish and hairy vetch. The results, in this case, were more significant when germitest paper was used than sand as substrate. In relation to the compounds, it was detected the presence of tannins, steroids and triterpenoids, derived from coumarin, spumidic saponin and alkaloids. So, based on the observed positive changes, it is recommended to use these cover crops in crop rotation with soybeans to reduce B. pilosa weed